Die Gefühlsgemeinschaft der AfD : Narrative, Praktiken und Räume zum Wohlfühlen - Spissinger, Florian (2024)
How does the AfD manage to make its supporters feel comfortable with a party that many people find repulsive? Florian Spissinger ethnographically observed lecture events, regulars' tables and AfD election campaign stands and conducted on-site interviews. What became evident was a new-right affective community against which critical objections bounce off without effect and for which the rejection of immigration and climate protection feels good and clever.